Determining the limits of geometrical tortuosity from seepage flow calculations in porous media. Issue 1 (December 2014) - Uribe, David; Osorno, Maria; Sivanesapillai, Rakulan; Steeb, Holger; Ruiz, Oscar
Abstract Recent investigations have found a distinct correlation of effective properties of porous media to sigmoidal functions, where one axis is the Reynolds number Re and the other is the effective property dependent of Re, Θi=Si(Re). One of these properties is tortuosity. At very low Re (seepage flow), there is a characteristic value of tortuosity, and it is the upper horizontal asymptote of the sigmoidal function. With higher values of Re (transient flow) the tortuosity value decreases, until a lower asymptote is reached (turbulent flow). Estimations of this parameter have been limited to the low Reynolds regime in the study of porous media. The current state of the art presents different numerical measurements of tortuosity, such as skeletization, centroid binding, and arc length of streamlines. These are solutions for the low Re regime. So far, for high Re, only the arc length of stream lines has been used to calculate tortuosity. The present approach involves the simulation of fluid flow in large domains and high Re, which requires numerous resources, and often presents convergence problems. In response to this, we propose a geometrical method to estimate the limit of tortuosity of porous media at Re → ∞, from the streamlines calculated at low Re limit. We test our method by calculating the tortuosity limits in a fibrous porous media, and comparing the estimated values with numerical benchmark results. Ongoing work includes the geometric estimation of different intrinsic properties of porous media. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)